Paying for convenience: Comparing the cost of takeaway meals with their healthier home-cooked counterparts in New Zealand - MacKay, S.; Vandevijvere, S.; Xie, P.; Lee, Andy; Swinburn, B. (Cambridge University Press, 2017)
© 2017 The Authors. Objective Convenience and cost impact on people's meal decisions. Takeaway and pre-prepared foods save preparation time but may contribute to poorer-quality diets. Analysing the impact of time on relative cost differences between meals of varying convenience contributes to understanding the barrier of time to selecting healthy meals. Design Six popular New Zealand takeaway meals were identified from two large national surveys and compared with similar, but healthier, home-made and home-assembled meals that met nutrition targets consistent with New Zealand Eating and Activity Guidelines. The cost of each complete meal, cost per kilogram, and confidence intervals of the cost of each meal type were calculated. The time-inclusive cost was calculated by adding waiting or preparation time cost at the minimum wage. Setting A large urban area in New Zealand. Results For five of six popular meals, the mean cost of the home-made and home-assembled meals was cheaper than the takeaway meals. When the cost of time was added, all home-assembled meal options were the cheapest and half of the home-made meals were at least as expensive as the takeaway meals. The home-prepared meals were designed to provide less saturated fat and Na and more vegetables than their takeaway counterparts; however, the home-assembled meals provided more Na than the home-made meals. Conclusions Healthier home-made and home-assembled meals were, except one, cheaper options than takeaways. When the cost of time was added, either the home-made or the takeaway meal was the most expensive. This research questions whether takeaways are better value than home-prepared meals.